Síntese de derivados do Cardanol para desemulsificação de petróleo e inibição da precipitação asfaltênica - Feitosa, Filipe Xavier (2018)
The complex mixture of hydrocarbons constituting petroleum provides the possibility of numerous products and consumer goods of various kinds, but it is also the origin of several problems related to elevation, production and refining. In industry, these problems are mitigated with the use of chemical additives in the various problems presented, be it corrosion, inorganic inscrustrations, formation of emulsions, among other problems. Whether it is the desorption of asphaltenes at interfaces or the inhibition of asphaltenes precipitation, the use of chemical products, of a polymeric and sometimes surfactant nature, plays a fundamental role in the prevention and remediation of problems related to guarantee of flow. In this work, the knowledge obtained from model assays, containing only heptane, toluene and asphaltenes in an attempt to simulate some colloidal properties, tries to be applied to systems containing crude oil. Additionally, modifications of cardanol, derived from cashew nut liquid (LCC), are applied as emulsion-forming inhibitors, de-emulsifiers and asphaltene precipitation inhibitors. By evaluating the effects of different sources of asphaltenes and their colloidal properties on the oil-water interfacial action, on the stability of emulsions and on the precipitation of asphaltenes it is noticed that the addition of n-heptane alters the colloidal state of the asphaltenes and that the asphaltenes precipitated particles exhibit interfacial behavior dependent on changes in the organic phase, addition of n-heptane, and by changes in the salinity of the aqueous phase. Addition of salt, 10 g NaCl / L, to the systems reduced interfacial tension for all concentrations of asphaltenes studied. Higher variations occurred for asphaltenes systems from sample I studied (ASF-I) and those from sample M (ASF-M). For two of the precipitated asphaltenes (ASF-L and ASF-M) it was confirmed that aggregates of asphaltenes have higher interfacial tensions and these participate in the mechanism of stability of emulsions. The amount of water dissolved in a given pattern may contain precipitate of the precipitated asphaltene type, provide asphaltene samples which stabilize the emulsion formulated together containing heptane and toluene as the organic phase (heptol) more intensely than the others, even with subjects degrees of aggregation. It was not possible to simulate an emulsion solution in medium and real, but an emulsion application in Reals. NaCl at concentrations of 240 g / L and 120 g / L prevent the oil emulsion being stable at 60 ° C for two hours. The L Oil sample appears to "withstand" the highest salinities and maintain its stability. This is indicative of lower compressibility of dual layer water, using the effects are prevalent in systems model. Regarding the alterations of the LCC derivative studied, ethoxylated cardanol responds more efficiently not pH 10. Ethoxylated resin acts in a way that neutral pH obtains better water separations. The physical parameters of the compounds influence the stability of the emulsions, as expected; pH can reverse the expected stability, followed by chemistry in the emulsion stabilization process. A has in the same has been applied in the determination of inhibitors and inhibitors has been determined, in the moment of the stabilizing the emulsion is decoder stabilosed the nonexistent? dissolution of asphaltenes.